Scarpetta - Cornwell, Patricia Daniels, 1953- (Kay Scarpetta, 2009)
Leaving behind her forensic pathology practice in South Carolina,Kay Scarpetta takes up an assignment in New York City,where the NYPD has asked her to examine an injured patient in a psychiatric ward.The handcuffed and chained patient,Oscar Bane,has specifically asked for her,and when she literally has her gloved hands on him,he begins to talk -and the story he has to tell turns out to be one of the most bizarre she has ever heard.He says his injuries were sustained in the course of a murder .that he did not commit.Is Bane a criminally insane stalker who has fixed on Scarpetta?Or is his paranoid tale true,and it is he who is being spied on, followed and stalked by the actual killer?The only thing Scarpetta knows for certain is that a woman has been tortured and murdered - and that more violent deaths will follow...